Fresh from the garden : an organic guide to growing vegetables, berries, and herbs in cold climates - Whitman, John, 1944- (University of Minnesota Press, 2017)
"Fresh is simply best. To get the tastiest, most nutritious produce, you have to grow your own, and in a cold climate this presents unique challenges. Fresh from the Garden will help you extend the growing season to produce the best vegetables, berries, and herbs, right in your own backyard. The guide includes more than 150 edible plants and helps you decide which varieties to choose; where and how to plant, tend, and harvest them; and what to do with your bounty. Fresh from the Garden is a clear, concise guide, with nutrition information tables and hundreds of helpful color photographs. Drawing on more than fifty years of gardening--and nearly as many years writing on the subject--John Whitman describes various methods of planting to make the most of different sites, whether in containers, raised beds, or on level ground, and takes into consideration the abbreviated growing season and longer summer days. He discusses the merits of starting from seed indoors or outdoors, the making and uses of compost, and measures for keeping a garden healthy, from mulching and fertilizing to crop rotation and winter protection. Included in his wealth of knowledge is a generous listing of more than 1,700 varieties of vegetables, berries, and herbs, from the best known to the highly unusual, including hybrid and heirloom varieties. He covers the specifics of cultivation, nutritional values, storage techniques, and culinary usage. Dedicated to organic practices, for the health of gardener and garden alike, the information and advice in Fresh from the Garden will enrich the experience of cold climate gardeners,"--Amazon.com.